KOMPOSTER SAMPAH INDIVIDUAL RUMAH TANGGA UNTUK PENGELOLAAN SAMPAH PERMUKIMAN DI KELURAHAN WAJO BARU KECAMATAN BONTOALA KOTA MAKASSAR - Hamdy, Muhammad Awaluddin; Asnur, Syam Fitriani (Jurnal Ilmiah Ecosystem, 2020)
Solid waste management problems become very serious in urban areas due to the complexity of the problems faced and high population density, so that solid waste management is often prioritized for handling in urban areas.The current condition of Makassar City is experiencing very rapid development, the construction of facilities, infrastructure and facilities as well as the city's infrastructure that makes Makassar City the gateway to eastern Indonesia. Seeing this development, Makassar City needs the same priority in waste services as other cities. Wajo Baru Village is one of the areas in the Bontoala District of Makassar City consisting of 10 (ten) RWs and 42 RTs. The parts of the Bontoala Subdistrict region which include the Wajo Baru Village are stipulated in the Makassar City Regional Spatial Plan in part of the downtown area, residential area, and trade area. Solid waste conditions in Wajo Baru village indicate that the condition of the availability of garbage (container) infrastructure is not yet available so that people throw garbage in any place. The methodology for implementing this program is community based. This community-based planning program is in accordance with the phenomenology paradigm, which is planning by prioritizing empirical conditions as a basis for planning. The results of waste development in Wajo Baru Village are directed by the concept of integrated waste management, which is sorting organic and inorganic waste that can be of productive value. Organic waste is processed through household composter technology and manual composter processing systems. To support this, each building is equipped with two landfills to separate organic and inorganic waste and the provision of trash facilities. Organic waste is processed in a garbage chopper machine and then processed in a garbage composter so that it can be used for fertilizer, while inorganic waste is collected in a trash can then transported to a waste treatment plant for sorting. Waste that is of productive value is placed in a garbage bank that can be sold or recycled into handicrafts while waste that is not of productive value is carried out with a garbage composter system.